Evaluation of Intestinal Helminth Infection Among Stunting Children Under Five Years of Age in Bendung Village, Kasemen District, Banten: A Cross-Sectional Study - Trasia, Reqgi First; Fitriani, Nabilla; Djuardi, Yenny (Indonesian Journal of Advanced Research, 2025)
One of the risk factors for stunting is intestinal helminth infection. Soil-Transmitted Helminth (STH) is the most common worm that infects the human intestine. Evaluation of the relationship between intestinal helminth infection and stunting in children under five years will be carried out in Bendung Village, Kasemen District, Banten. This research is a cross-sectional study conducted in Bendung Village, Kasemen District, Banten. Intestinal helminth infections were examined using the Kato-Katz method. Socioeconomic status is measured based on the Kuppuswamy’s socioeconomic scale. Immunization status is obtained from the Mother & Child Card (KIA). The statistical analysis used was bivariate Chi-Square and Fisher’s Exact tests. The prevalence of stunting among 12-59 months children in Bendung Village, Kasemen District, Banten was 48.6%. The prevalence of intestinal helminth infection was 41.7% (each species A. lumbricoides 33.3%, T. Trichiura 1.4%, hookworm 1.4%, mixed infections of A. lumbricoides and T. Trichiura 1.4%, mixed infections of A. lumbricoides and hookworm 1.4%). Intestinal helminth infection were significantly associated with stunting in children under five years. The results of this study indicate a high rate of stunting and intestinal helminth infection in children under five years in Bendung Village. Intestinal helminth infection has a negative impact on the growth of children under five years.